Single-ended fault location technique on a radial distribution network using fault generated current signals - Hizam, Hashim; Crossley, P. A. (Federation of Engineering Institutions of Islamic Countries, 2006)
High frequency signals generated due to faults contain information which could be utilised to locate the faults. Based on the principle of reverberation of waves on power network, the high frequency signature of the current signals are related to known reflection points exist in the network. From these the fault section and the probable location of the fault can be identified. The probable location is then used within a power system simulator that models the network. The simulated current waveforms at the probable locations are then cross-correlated against the signals captured. If the identified location is correct, the high frequency signature in the simulated waveform will be similar to that observed in the measured waveform and the cross-correlation value will have a high positive value. If the signatures differ, the cross-correlation value will be small. Simulation studies using PSCAD/EMTDC and analysis using cross-correlation indicate that locating faults on a radial distribution feeder is a possibility using a single ended travelling wave measurement method.